(untitled) (Research, Society and Development, 2024)
Introduction: Dengue is an arboviral disease caused by the serotypes DENV-1, DENV-2, DENV-3, and DENV-4, which primarily spreads through the bite of the Aedes aegypti mosquito. This disease poses a significant challenge to public health, with approximately 390 million infections worldwide each year, of which around 20,000 result in death, highlighting a greater vulnerability in the younger population that has less prior exposure to the virus. Objective: To highlight the impacts of dengue on Brazilian public health between 2023 and 2024. Methodology: A narrative literature review based on 10 scientific articles published between 2023 and 2024. Results and Discussion: Between 2023 and 2024, dengue caused significant impacts on Brazilian public health, reflecting a considerable increase in disease incidence and strain on the healthcare system. Early recognition of symptoms is crucial, as well as the implementation of protocols that integrate vaccination into prevention strategies. The increasing resistance of the Aedes aegypti vector to traditional control measures necessitates new approaches that include biotechnology and environmental management. Furthermore, combining vaccination, community awareness, and improvements in sanitation conditions is essential to mitigate the impacts of dengue and enhance epidemic response. Conclusion: An integrated and sustainable approach is crucial to tackle the challenges posed by dengue, ensuring the protection of public health and reducing the economic burden associated with the disease.